PELATIHAN GAYA KEPEMIMPINAN DALAM BERORGANISASI DAN GAYA NEGOSIASI DALAM MEMASARKAN PRODUK DI MEDIA SOSIAL KEPADA MAHASISWA S-1 KOMUNIKASI STISIPOL CANDRADIMUKA - Santoso, Budi; Herfriady, Herfriady (Lembaga Penelitian dan Pengabdian Masyarakat STISIPOL Candradimuka Palembang, 2020)
Leadership value training and the processes that must be passed by someone to become a leader have undergone many shifts. The evolution of thoughts and social life that continues to grow has made the modern human paradigm change in viewing the concept of leadership. Participative leadership style, leadership in organizational change and how to make the right decision. Before holding a negotiation, you must first review the theme of the negotiation so that the negotiation process runs smoothly and there is no shortage of ideas to provide solutions. To make it easier to study the negotiation theme, use the 5W+1H formula and answer the possibilities of the formula. After this training, it is hoped that the administrators of the S-1 STISIPOL Candradimuka students will have and demonstrate leadership behavior skills and are good at negotiating who are ready to take on challenges and can inspire students in the school environment.